Applications, impacts and consequences of botulinum toxin usage in medicine - Kiełt, Weronika; Kozłowska, Julia; Broniec, Gabriela; Wajdowicz, Barbara; Kudła, Aleksandra; Czapiewska, Rozalia; Dziewulska, Aleksandra; Wróbel, Aleksandra; Pacek, Laura; Kowalska, Klaudia (Journal of Education, Health and Sport, 2024)
Introduction Botulinum toxin is a neurotoxin produced by the gram-positive bacteria Clostridium botulinum. Botulinum toxin has found great interest in the field of aesthetic medicine, but it has many other applications in other areas of medicine. Aim of the study The aim of this comprehensive review is to provide an overview of the usage of botulinum toxin in medicine, with a focus on specific areas of medicine. Attention will be paid to the safety of the use of this substance, taking into account its molecular structure and mechanism of action. Materials and methods An analysis of the scientific articles available in the Pubmed, Google Scholar and web of science databases was performed. Recent publications which most appropriately encompassed the issues under discussion have been selected for the purpose of this study. The process of search was carried out with the following keywords: neurotoxin, botulinum toxins, botulism, muscle paralysis. Summary Despite numerous studies, there is ample room for further research into the safety of using botulinum toxin in patients as well as new therapies with this substance. Botulinum toxin is a neurotoxin that is widely used in medicine, but has many side effects.